Source of Information in Regard of Starting Breast_Feeding in Baghdad - Sinan Makki; Dawood M. AL-thamery (مجلة كلية الطب, 2007)
This study. was done on three hundred mothers who has a child less than 5 year old in ALNahryn University Teaching Hospital for the period of three months 1-1-2001 to 31-3-2001. The study showed that 48% were Breast-feeding, 11% Bottlefeeding, & 41% Mixed breast and bottle-feeding. The family plays a major role (97.2%) in deciding the type of feeding and the doctor role was only 2% in that regard and 21.2% in advice for artificial feeding. The study also showed that there is a decline in breast feeding among -the three generations studied 100%, 96.4%, 48%; which represent around 52% o decline in breast feeding.